Controller design for PV experimental bench with ADRC strategy supervised by Labview created interface - Naoufel Khaldi; Youssef Barradi; Khalida Zazi; Malika Zazi (International Journal of Power Electronics and Drive Systems (IJPEDS), 2021)
The converter control scheme plays an important role in the performance of maximum power point tracking (MPPT) algorithms. In this work, a model has been analysed, designed and simulatedon Power Simulator software and in Matlab Simulink.A hardware implementation using a microcontroller (Arduino Mega 2560 based on ATmega2560) is provided, that operateson feedback from a PV panel voltage and current to control the operation of DCDC converter in order to draw maximum power. Newactive disturbance rejection control (ADRC) algorithm is required to extract the maximum power of the solar energy. This MPPT controller incorporates a boost topology that ensuresa two continuous battery in series (12V, 5Ah) charging in various conditions. The whole of the results shows in one hand that the converter efficiency is very satisfactory, and in the other hand a very good agreement between the results simulated and those experimental in terms of performance. The proposed system is designed in Proteus, and implemented on hardware with a graphical user interface built throughout Labview software.